Grid Integration of Hybrid Energy System for Distribution Network - Bayu, Atinkut; Anteneh, Degarege; Khan, Baseem (Distributed Generation & Alternative Energy Journal, 2021)
In the real world, most countries generate electricity from fuel, which has its own disadvantages. To minimize the usage of fuels, economic, social and environmental effects should be studied and focus should be given on the development of alternative power sources, such as solar photovoltaic (PV), wind energy, micro-hydro power and others. This paper focuses on the use of solar photovoltaic generation in conjunction with wind turbines to generate electrical energy. Further, this work studies the hybrid electrical energy generation system for the selected power network for Debre Berhan City. The developed hybrid system is connected to the grid to supply the load. Modeling of the power network and the components of the hybrid power network is performed by using MATLAB software. Results show the outputs of wind and solar PV generation are 168.5 kW and 173.3 kW, respectively, to supply the demand of 200 kW. Therefore, the most suitable option to supply the demand is the combination of solar PV and wind turbines, which produces 357.8 kW